Analisis Implementasi Penguatan Profil Pelajar Pancasila dalam Kurikulum Merdeka Mandiri Berubah pada Pembelajaran IPA SMP berdasarkan Respon Siswa - SUTICHA, ENTIK; Hindriana, Anna Fitri; Nur, Sofyan Hasanuddin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to find out how the implementation of strengthening Pancasila student profiles in the independent curriculum in junior high school science learning is based on student responses. This research is a qualitative research. The type of data presented in qualitative research is primary data obtained from student response questionnaires. The population in this study is all junior high schools in Cirebon city that have implemented the independent independent curriculum, with a total of 30 schools consisting of 13 public schools and 17 private schools. School sampling in this study used a proportional random sampling technique. Sampling in this study the authors used a sampling method with a ratio of 30%, so the number of school samples was 9 schools with 4 public schools and 5 private schools. In collecting data, the writer uses indirect data collection techniques in the form of a Linkert Scale questionnaire instrument. Based on the results, Strengthening Pancasila Student Profiles in the independent curriculum based on students' responses stated that in the learning process facilitating the development of Pancasila student profiles, students agreed to gain an understanding of the science context according to CP and learning and assessments that support literacy and numeracy skills, gain an understanding of the science context according to with the learning outcomes of Phase D, carry out activities or assignments that are relevant to the skills on learning outcomes of Phase D and Pancasila Student Profiles, get learning activities with literacy and numeracy, and students agree to get an assessment in the science learning process conducted by the teacher. So it can be concluded that the implementation of strengthening the profile of Pancasila students in the independent independent curriculum changed to Middle School Science learning has been implemented well in the Science learning process by teachers and can be understood by students.